The Influence of Promotional Strategies, Product Design, and Halal Labels on the Purchase Decision of King Kebab and Rantauprapat Burger Culinary - Dila Nafila Saputri Ayu; Bayu Eko Broto; Nurintan Asyiah Siregar (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of promotional strategies, product design, and halal labels on purchasing decisions on the culinary king of kebabs and rantauprapat burgers. The population in this study is the culinary consumer of the king of kebabs and rantauprapat burgers. The number of samples in this study amounted to 96 samples. The sampling technique used was non-probability sampling and the researcher used accidental sampling. The testing technique used in this test is validity, reliability, multiple linear regression, normality test, heteroscedasticity test, multicoloniarity test and coefficient of determination. TEST The hypothesis uses the t-test to prove the effect of the independent variable on the dependent variable. The test results in this study indicate that promotional strategies affect purchasing decisions, product design affects purchasing decisions, halal labels affect purchasing decisions. Simultaneously promotion strategy, product design, halal label affect purchasing decisions.